A homozygous nonsense mutation (c.214C→A) in the biliverdin reductase alpha gene (BLVRA) results in accumulation of biliverdin during episodes of cholestasis. Issue 4 (28th January 2011) - Nytofte, Nikolaj S; Serrano, Maria A; Monte, Maria J; Gonzalez-Sanchez, Ester; Tumer, Zeynep; Ladefoged, Karin; Briz, Oscar; Marin, Jose J G
Abstract : Background: Green jaundice is a rare finding usually associated with end-stage liver disease. Objective: The authors investigated two unrelated Inuit women from different geographical areas in Greenland who had episodes of green jaundice associated with biliary obstruction. Methods and results: The crises were accompanied by increased biochemical markers of cholestasis, together with absent or moderate hyperbilirubinaemia. In contrast, high-performance liquid chromatography tandem mass spectrometry showed hypercholanaemia and high concentrations of biliverdin IXα in serum, urine, bile and milk. Hyperbiliverdinaemia disappeared after surgical correction of the cholestasis. Analysis of the coding sequence of the biliverdin reductase alpha (BVRα) gene ( BLVRA ) detected three single-nucleotide polymorphisms: c.90G→A, c.214C→A and c.743A→C, which result in p.Ala3Thr, p.Ser44X and p.Gly220Gly, respectively. With the use of TaqMan probes, homozygosity for c.214C→A was found in both patients. Both parents of one of these patients were heterozygous for the inactivating mutation. Her brother was homozygous for normal alleles. Although her sister was also homozygous for the c.214C→A mutation, she had never had hyperbiliverdinaemia or cholestasis. With the use of human liver RNA, the BVRα coding sequence was cloned, and the variant containing c.214C→A was generated by site-directed mutagenesis. Both proteins were expressed in human hepatoma liver cells and Xenopus laevis oocytes. Immunoblotting, immunofluorescence and functional assays of BVRα activity revealed that the mutated sequence generates a truncated protein with no catalytic activity. Conclusion: This is the first report of a homozygous BLVRA inactivating mutation indicating that the complete absence of BVRα activity is a non-lethal condition, the most evident phenotypic characteristic of which is the appearance of green jaundice accompanying cholestasis episodes.